Arthroscopic ankle arthrodesis: clinical results - Silva, Bruno Air Machado da; Vasconcelos, Jonatas Barbosa; Bucar, Hamilton Leão; Tavares, Pedro Henrique de Souza; Vitorino, Ricardo; Fernandes, Lucas (Journal of the Foot & Ankle, 2025)
Objective:Evaluate the clinical outcome of arthroscopic ankle arthrodesis. Methods:This is a retrospective study, involving 17 patients with ankle arthrosis who did not improve with conservative treatment. These patients underwent ankle arthrodesis via ankle arthroscopy between January 2015 and December 2020, all performed by the same surgeon. The American Orthopedic Foot and Ankle Society (AOFAS) hindfoot and ankle score will be used for functional assessment of patients and patient satisfaction and quality of life will be assessed by the Patient-Reported Outcomes Measurement Information System (PROMIS Global – 10), with maximum of 20 points per item evaluated. Results:The average surgery time was 81.4 ± 7.9 minutes and all patients were discharged on the day following surgery. The average time for consolidative arthrodesis was 10.8 ± 1.9 weeks. The preoperative ankle and hindfoot AOFAS score improved when compared to that obtained at the last consultation, in a statistically significant way (from 55.8± 3.2 to 89± 2.1). The physical status measured by PROMIS preoperatively increased from 9.8 ± 1.2 to 18.2 ± 1.3. Just as mental health increased from 8.9 ± 1.1 to 17.9 ± 1.5. Conclusion:Ankle arthrodesis through arthroscopy is a less invasive option that has shown significant improvement in the rearfoot-ankle AOFAS score and PROMIS, high union rate. Level of evidence Level IV; Therapeutic studies; Case series.